1991
DOI: 10.2165/00003088-199121020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ajmaline Test in a Patient with Chronic Renal Failure

Abstract: Pharmacokinetic and pharmacodynamic properties were studied after intravenous administration of ajmaline 1 mg/kg in an anuric patient, who underwent the electrophysiological ajmaline test. The magnitude and rate of onset of the typical electrophysiological effects of ajmaline (prolongation in atrio-Hisian and His-ventriculum conduction times) were within the range of normal values. The plasma concentration curve showed a triexponential decay with half-lives as follows: initial phase (t1/2 alpha) 1.34 min, fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Recently, we studied the pharmacokinetics of ajmaline in an anuric patient undergoing periodic haemodialysis (Padrini et al 1991) and the values of total body clearance and terminal half-life found (17.00 mllmin/kg and 4.3 hours, respectively) were within the range reported here (CL 6.30 to 17.27 mllmin/kg; t\l214.6 to 16.5 hours). This confirms the minimal role played by the kidney in ajmaline elimination.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Recently, we studied the pharmacokinetics of ajmaline in an anuric patient undergoing periodic haemodialysis (Padrini et al 1991) and the values of total body clearance and terminal half-life found (17.00 mllmin/kg and 4.3 hours, respectively) were within the range reported here (CL 6.30 to 17.27 mllmin/kg; t\l214.6 to 16.5 hours). This confirms the minimal role played by the kidney in ajmaline elimination.…”
Section: Discussionsupporting
confidence: 80%
“…However, our results have shown that, in a group of patients who underwent the ajmaline test because of suspected paroxysmal AV block, the t\l21 of the drug averaged 7.3 hours. As discussed in a previous paper (Padrini et al 1991), such a discrepancy might be attributed to the less sensitive assay methods used in the past, which did not permit plasma concentration decay to be followed for long enough to detect the true elimination phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations